Biochemical characterization of pink husked coconut types - Thomas, Regi J.; Shareefa, M.; Harsha, H.; Karun, Anitha (Journal of Plantation Crops, 2021)
Coconuts with various traits are available in different coconut growing countries. The pink husk is one such trait that has already been reported in coconut. There is a demand for tender nut water from pink husked types of coconut to treat hepatitis by traditional medicinal practitioners. Present studies were carried out to characterize pink husked types identified in Guam Tall variety of coconut. There were no morphological differences with respect to the nut characters between pink and non-pink husked types. Biochemical characterization of pink husked types revealed significantly higher total phenol content in the tender nut water of pink husked types than normal husked types. A significantly higher protein content of 86 mg 100 mL-1 was noted in pink husked type, compared to normal husked type with 58.7 mg 100 mL-1. Higher free radical scavenging activity based on DPPH assay with pink husked type was recorded with an IC50 value of 266.7 compared to normal type with an IC50 value of 358. Similarly, phosphomolybdate assay also revealed higher scavenging activity of pink husked type based on the IC50 value of 415.2 compared to 637.9 observed in normal husked type. Anthocyanin content of 25.98 mg 100g-1 fresh weight was noted in the exocarp of pink husked types, and it was negligible in normal husked type. These results justify the use of pink husked coconuts in various traditional medicines. There is tremendous potential for exploiting pink husked types of coconut in the pharmaceutical industry.